Cervical cancer in women of the Far Eastern Federal District (morbidity and mortality) - T. N. Chimitdorzhieva (Опухоли женской репродуктивной системы, 2020)
Objective: to analyze the incidence and mortality of cervical cancer in the Far Eastern Federal district (FEFD) in 2008–2018.Materials and methods. To assess the incidence and mortality of cervical cancer among women residing in FEFD, we used annual reports of P. Hertzen Moscow Oncology Research Institute – branch of the National Medical Research Radiology Center, Ministry of Health of Russia, for 2008–2018. We evaluated extensive and standardized parameters (per 100,000 population; 0/0000) calculated using the direct method (world standard). The prognosis was based on the 11-year dynamics of the incidence and mortality; regression coefficients were calculated using the standard method. Data analysis was performed using the Statistica 8.0 and Microsoft Excel 2003 software with a significance level of p £0.05. We evaluated the incidence and mortality of cervical cancer among women of FEFD registered between 2008 and 2018: during a 5-year period (2008–2012) and a 6-year period (2013–2018) for the whole region, as well as for individual administrative territories.Results. We found that the incidence of cervical cancer in FEFD was higher than its national incidence (14.3 ± 0.10/0000) and was steadily increasing in all administrative centers of FEFD. The highest incidence was observed in Zabaikalsky Krai (32.6 ± 1.90/0000, which is 2.3 times higher than national incidence). The quickest growth of cervical cancer incidence was registered in the Republic of Buryatia (69.6 %; growth rate 6.5 % (p £0.05)). This territory was also characterized by the highest mortality (11.4 ± 0.50/0000, which is 2.2 times higher than national mortality (5.3 ± 0.20/0000) (p <0.01)).Conclusions. The analysis of the cervical cancer incidence and mortality in FEFD demonstrated their steady increase, which makes the issues of disease prevention and early diagnosis highly relevant and indicates a clear need to activate vaccination and screening programs.